2004
DOI: 10.1212/wnl.62.2.269
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutational dynamics in myotonic dystrophy type 1 males

Abstract: Progenitor allele length is a major modifier of the mutational dynamics of the DM1 repeat in the male germline, but surprisingly age is not. Therefore, other as yet unidentified modifiers must be responsible for the considerable residual interindividual variation that cannot be accounted for by these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 19 publications
3
31
0
Order By: Relevance
“…This effect was much more pronounced for females, and was only apparent for males carrying pre-and proto-mutations (o80 repeats). These observations are consistent with the intraclass correlation between siblings, which was significant for female transmissions, but was not detectable for paternal transmissions; consistent with the very high levels of intra-individual variation observed by direct sperm analysis 25,30,33 and suggesting that inter-egg variation is less pronounced. Our analyses have also confirmed that the main driver of the size of the intergenerational length change is also parental ePAL.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This effect was much more pronounced for females, and was only apparent for males carrying pre-and proto-mutations (o80 repeats). These observations are consistent with the intraclass correlation between siblings, which was significant for female transmissions, but was not detectable for paternal transmissions; consistent with the very high levels of intra-individual variation observed by direct sperm analysis 25,30,33 and suggesting that inter-egg variation is less pronounced. Our analyses have also confirmed that the main driver of the size of the intergenerational length change is also parental ePAL.…”
Section: Discussionsupporting
confidence: 86%
“…10,13,[15][16][17][18][19] Full mutations (479 repeats) in males are highly unstable, but appear to be more likely to contract; consistent with direct sperm analyses. 25,30,33 In females, pre-and protomutations are relatively stable, but full mutations are much more unstable and biased towards much larger expansion than in males, consistent with the excess of transmitting mothers of CDM. 10,13,20,21 However, transmissions from mothers with very long alleles (4249 repeats) are less well explained by maternal ePAL and, as in males, appear to be more likely to contract.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations